Professional Experience of Practiting Lawyers in Law Enforcement: A Dialectical Assessment - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR) Publisher, 2022)
As a result of the conducted research, the author comes to the conclusion that the personal professional experience of law enforcement of law enforcement officers of law enforcement bodies, formed in the process of upbringing, education and practical activities and generalizing the relevant professional knowledge, skills and skills of law enforcement actors, on the one hand, helps them to orient in the evidentiary information, to carry out from it theselection of everything necessary for the correct resolution of a particular legal case with However, on the other hand, it is also necessary to take into account the fact that the same legal situations, on which professional experience is guided, tend to create, as a rule, the stereotyping of intellectual processes, the template actions and operations of these individuals, which make it difficult to see the uniqueness of that or other life event, lack of criticality, arrogance and complacency, oblivion of the fact that every legal matter is individual, a manifestation of the sense of omniscience and hence its own the infallibility can lead to accusatory bias and cause serious errors in the process of law enforcement.